Detection of Hidden Defects Induced by Thermomechanical Processing of Aluminum Substrates for Sensor Devices Using a Scanning Kelvin Probe - A. L Zharin; I. V. Gasenkova; A. K. Tyavlovsky; N. I. Mukhurov; S. I. Spitski (Приборы и методы измерений)
The object of the study was aluminum substrates for creating sensor devices based on anodic aluminum oxide, which underwent mechanical processing in the form of grinding and straightening. The subject of the study was the detection of residual mechanical stresses and other surface defects to assess the quality of this processing using the scanning Kelvin probe technique. The technique applied allows for the effective detection of residual plastic deformations of aluminum substrates resulting from their mechanical processing with a resolution sufficient to detect mechanical stresses associated with individual roughnesses.